Coulomb spin liquid in anion-disordered pyrochlore Tb2Hf2O7. Issue 1 (December 2017) - Sibille, Romain; Lhotel, Elsa; Ciomaga Hatnean, Monica; Nilsen, Gøran J.; Ehlers, Georg; Cervellino, Antonio; Ressouche, Eric; Frontzek, Matthias; Zaharko, Oksana; Pomjakushin, Vladimir; Stuhr, Uwe; Walker, Helen; et al.
Abstract The charge ordered structure of ions and vacancies characterizing rare-earth pyrochlore oxides serves as a model for the study of geometrically frustrated magnetism. The organization of magnetic ions into networks of corner-sharing tetrahedra gives rise to highly correlated magnetic phases with strong fluctuations, including spin liquids and spin ices. It is an open question how these ground states governed by local rules are affected by disorder. Here we demonstrate in the pyrochlore Tb2 Hf2 O7, that the vicinity of the disordering transition towards a defective fluorite structure translates into a tunable density of anion Frenkel disorder while cations remain ordered. Quenched random crystal fields and disordered exchange interactions can therefore be introduced into otherwise perfect pyrochlore lattices of magnetic ions. We show that disorder can play a crucial role in preventing long-range magnetic order at low temperatures, and instead induces a strongly fluctuating Coulomb spin liquid with defect-induced frozen magnetic degrees of freedom. Experimental studies of frustrated spin systems such as pyrochlore magnetic oxides test our understanding of quantum many-body physics. Here the authors show experimentally that Tb2 Hf2 O7 may be a model material for investigating how structural disorder can stabilize a quantum spin liquid phase.